Pengaruh Kualitas Layanan dan Penanganan Keluhan terhadap Loyalitas Nasabah Bank Syariah Indonesia (BSI) KCP Kuala Tungkal - Mohan Tridipa Syamta; Ridhwan; Yusuf Zaini Aprizal (JOURNAL OF SHARIA ECONOMICS, 2026)
This study aims to determine the effect of service quality and complaint handling on customer loyalty at Bank Syariah Indonesia (BSI) KCP Kuala Tungkal. The research is motivated by the increasing level of competition in the banking industry, where these two variables are considered the main factors that distinguish one bank from another in maintaining customer loyalty. This study employs a quantitative approach using multiple linear regression analysis with IBM SPSS version 25. The sample consisted of 100 respondents who are customers of BSI KCP Kuala Tungkal. The results show that service quality (t = 0.986 < 1.984) has no significant effect on customer loyalty, while complaint handling (t = 8.653 > 1.984) has a significant positive effect. Simultaneously, service quality and complaint handling together have a significant effect on customer loyalty (F = 62.017 > 1.984). Thus, fast, fair, and empathetic complaint handling becomes the dominant factor in building customer loyalty at BSI KCP Kuala Tungkal.